Holder Zygmund Space Techniques to the Navier-Stokes Equations in the Whole Spaces (Journal of Partial Differential Equations, 2000)
With the use of Hölder Zygmund space techniques, local regular solutions to the Navier-Stokes equations in R^n are shown to exist when the initial data are in the space {a|(-Δ)^{-β/2}a ∈ C^0(R^n)^n}\quad(0 < β < 1)
Keywords: :Navier-Stokes equations; local solutions: Hölder Zygmund spaces